Adaptasi Budaya Etnis Tionghoa di Meulaboh Aceh Barat (Studi : Masyarakat Tionghoa Non Muslim) - Fahriza Murti; Triyanto Triyanto (Jurnal Community, 2018)
There are almost no area where there are no ethnic Chinese, including Meulaboh Aceh Barat. Its existence is always interesting to learn because there are always different problems of interaction with the majority of the locals. His case is often related to preserving his minority and cultural identity, which is always different or even contrary to local culture. The problem of this work is how to adapt ethnic minorities to maintain their identity in the community. The method used in this research is a qualitatif method with the technique of determining the informant using the snowball sampling technique. The results showed that the adaptation of Chinese ethnic culture conducted in Meulaboh by interacting naturally with the surrounding community with organizations leading to the Hakka and daily activities very closely with them as trademarks of the Chinese, such as the use of clothing, religious events, and others.